SIMULASI PENGARUH LUAS PERMUKAAN ELEKTRODA TERHADAP TEGANGAN DAN KONSENTRASI PERMUKAAN ELEKTRODA PADA LEAD ACID REDOX FLOW BATTERY - Muhammad Ghufron; Silvi Hadila; Ervinka Felindia; Nikita Syaharani; Satria Pamungkas Panji Kumara; Irvan Fajar Hidayah; Gancang Saroja; Kurriawan Budi Pranata (ROTOR, 2021)
Energy storage systems (ESS) with large storage capabilities, easy made, and low cost are in high demand. Dynamic lead acid battery (DLAB) as a breakthrough design compared conventional lead acid batteries offers a solution to these problems. Two Dimensional (2D) DLAB simulations with surface area variations of 8 cm2, 12 cm2, 16 cm2 and 20 cm2 were successfully build using the principle of tertiary current distribution and Nerst-Planck Interface. The results for one cycle charge-discharge test showed that the increase in surface area succeeded in increasing the final charging voltage with a value of 2.16 V; 2, 21 V; 2.30 V and 2.32 V and increase the initial discharging voltage by a value of 1.58 V; 1.59 V; 1.60 V and 1.62 V respectively but did not affect the electrode surface concentration. Dynamic lead acid battery has high energy efficiency of 70.6% -71.5%.